Super dinosaur encyclopedia - Barker, Chris (Chris Tijani) (DK, 2020)
Presents the physical features, diet, habitat, and behaviors of dinosaurs and other prehistoric creatures, and features information about paleontology, fossils, and the history of life on Earth. Includes color illustrations, fact boxes, and a glossary.